Diagnóstico de refluxo gastroesofágico e doença de refluxo gastroesofágico: panorama clínico e epidemiológico de crianças atendidas em ambulatório especializado - Bianca de Oliveira Rodrigues; Mariana Menezes Rocha; Indhira Ribeiro Almeida; Katia de Miranda Avena (Sociedade Brasileira de Pediatria, 2024)
OBJECTIVE: Verify the prevalence of gastroesophageal reflux disease (GERD) among infants diagnosed with gastroesophageal reflux (GER) treated at a pediatric gastroenterology clinic, describing the clinical-epidemiological profile of the studied population. METHODS: This is an epidemiological, retrospective, cross-sectional study, based on the review of medical records of patients. Sociodemographic, clinical, epidemiological variables were recorded, such as age, sex, symptoms presented, type of nutrition, pediatricians prescription and medications used. RESULTS: There were studied 93 children diagnosed with GERD, whose prevalence of GERD was 45.2%. In GER and GERD groups, the most prevalent clinical-epidemiological profile was of boys (58.8% and 52.4%), aged over 6 months (54.9% and 61.9%). The onset of symptoms occurred at 3.0 months (IIQ [0.0-5.0 months]) in children with GER and at 2.0 months (IIQ [0.0-3.0 months]) in those with GERD. There was a higher prevalence of regurgitation (92.2%) and irritability (33.3%) among children with GER; and regurgitation (95.2%), cough and hiccups (28.6%, each) in those with GERD. Regarding drug treatment, there was a higher prevalence of the use of acid inhibitors (66.7%). CONCLUSION: A high prevalence of GERD was demonstrated, with regurgitation, cough and hiccups as the main symptoms. Infants on exclusive breastfeeding had a lower frequency of GER and GERD. Among the most used drugs, acid inhibitors were the most prescribed.